The effect of grazing on macrophytic communities of shallow rocky reefs in Lesvos - Kosma, Ioanna; Κοσμά, Ιωάννα (2020)
Intense grazing activity on macrobenthic communities is considered a driver, that can result to altered ecosystem functioning. Along the Mediterranean coasts, algal forests with complex structure are considered key habitats that form a fixed three-dimensional structure with high biodiversity and productivity. Overgrazing (i.e. the phenomenon where grazing rate prevails over algal growth rate) poses a serious threat and can lead to the reduction of habitat structure complexity and composition and the creation of rocky barren areas. A herbivore exclusion experiment was conducted at three stations along the southeastern part of Lesvos Island, in order to assess the potential grazing effects of sea urchin and fish herbivory on rocky substrate habitats. During the seven-month fieldwork (April to October 2017), PP-R frame cages (40×60×25cm) were installed on horizontal or slightly sloped surfaces and a plastic mesh was used for covering the cages (2×2cm opening). The selected stations had rocky substrate. At each site three replicates of two different treatment types and a control were placed between 1-5m depth. The two different treatment cages were: (1) fully-closed cages, which excluded both herbivorous fish and sea urchins from grazing activity and (2) open-top cages, which excluded only sea urchins. Moreover, no-cage surfaces with distinct markings, served as controls, where no restrictions were applied to herbivores. Monitoring with photoquadrats was conductedevery two weeks, in order to monitor the possible algal growth on the quadrats The results of the monitoring revealed that algal growth was higher inside both types of cages in contrast to the respective control surfaces. No significant differences were found between the two cage types in terms of total algal biomass. This suggests that herbivore fish grazing had minor effect compared to sea urchin grazing, which was found to be the most important grazing factor. Grazing activity has a strong impact on macroalgal communities, almost depleting canopy and erect algae, leading to turf dominated habitats that ultimately alter the composition to less complex and flattened in structure algal communities.